Design of a Loadbased Battery Discharge System in a Remote Island Using Marine Currents and Solar Energy as Energy Sources - Faanzir Faanzir,; Umar Umar,; Iswan Iswan, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This paper proposes a plan of electric system on a remote island that utilizes the power of marine currents and solar. The supply system is carried out in a decentralized battery and a centralized battery. The types of batteries used is Lithium-Ion (Li-Ion). The decentralized battery system and the centralized battery, refer to each customer's load power. Power customer loads using DC (Direct Current) equipment and lighting. The battery voltage used as a source is 48 V while the customer uses 12 V. The use of batteries as the main source to meet the electricity needs of various types of customers uses a maximum current of about 3.8 A.